Through creative lenses: Investigating the personal growth and well-being benefits of photography and videography - I Kadek Widhi Agastya; Cokorda Gede Putra Yudistira; Kasiani Kasiani; M. Agus Sutiarso; Fatema Sharmin (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2025)
This study explores the impact of photography and videography as hobbies on individuals' well-being, creativity, and personal growth. It investigates how these art forms contribute to skill development, self-expression, and social engagement, and examines the perceived benefits and challenges associated with practicing these hobbies. A qualitative approach is used, incorporating in-depth interviews with both amateur and professional photographers and videographers. Thematic analysis is employed to identify and analyse the patterns and themes within the interview data, providing a deeper understanding of the participants' experiences. Thematic analysis is conducted in a structured process. This includes initial familiarization with interview transcripts, generation of codes, identification of recurring themes, refinement of those themes, and the development of a comprehensive narrative. This process ensures that key insights relating to well-being, creativity, and personal growth are captured. The study concludes that photography and videography play a transformative role in enhancing well-being and mental health by offering stress relief and increasing life satisfaction. These hobbies also encourage creativity, self-expression, and skill development. Furthermore, they foster personal growth by boosting confidence, self-esteem, and social connections. Although challenges such as financial constraints and time commitments exist, the overall impact of these activities is overwhelmingly positive, contributing significantly to personal development and community involvement.